Pyricularia pennisetigena and P. zingibericola from invasive grasses infect signal grass, barley and wheat - Reges, Juliana Teodora De Assis; Negrisoli, Matheus Mereb; Dorigan, Adriano Francis; Castroagudín, Vanina Lilián; Maciel, João Leodato Nunes; Ceresini, Paulo Cezar (Escola de Agronomia/UFG, 2016)
ABSTRACT Fungal species from the Pyricularia genus are associated with blast disease in plants from the Poaceae family, causing losses in economically important crops such as rice, oat, rye, barley, wheat and triticale. This study aimed at characterizing the pathogenicity spectrum of P. pennisetigena and P. zingibericola to signal grass, barley and wheat, as well as comparing them with those from the species P. grisea and P. oryzae pathotype Triticum, which occur widely in the Brazilian agroecosystem. Twenty isolates of Pyricularia spp. were obtained from infected leaf samples of invasive plant species from wheat fields. The isolates classification into distinct Pyricularia species was done using molecular phylogeny based on actin and calmodulin genes. Pyricularia pennisetigena and P. zingibericola inoculated on plant leaves, at a concentration adjusted to 105 conidia mL-1, were pathogenic to signal grass, barley and wheat, with varying levels of aggressiveness.

RESUMO Espécies de fungos do gênero Pyricularia estão associadas com a doença brusone, em plantas da família Poaceae, causando perdas em culturas de importância econômica como arroz, aveia, centeio, cevada, trigo e triticale. Objetivou-se caracterizar o espectro de patogenicidade de P. pennisetigena e P. zingibericola em braquiária, cevada e trigo, bem como compará-los com os das espécies P. grisea e P. oryzae patótipo Triticum, de ocorrência generalizada no agroecossistema brasileiro. Foram testados 20 isolados de Pyricularia spp. obtidos de amostras de folhas infectadas de plantas invasoras de campos de trigo. A classificação dos isolados em espécies distintas de Pyricularia foi efetuada utilizando-se filogenia molecular baseada nos genes actina e calmodulina. Pyricularia pennisetigena e P. zingibericola inoculados em folhas, à concentração ajustada para 105 conídios mL-1, foram patogênicos a braquiária, cevada e trigo, com índices variáveis de agressividade.
Pyricularia pennisetigena e P. zingibericola de gramíneas invasoras infectam braquiária, cevada e trigo
Keywords: Pyricularia grisea; Pyricularia oryzae; blast disease; invasive plant species; inoculum sources; Pyricularia grisea; Pyricularia oryzae; brusone; plantas invasoras; fontes de inóculo